STUDY OF PITUITARY GLAND EXTRACT UTILIZATION FROM STRIPED CATFISH WASTE FOR REPRODUCTION PERFORMANCE IMPROVEMENT OF NORTH AFRICAN CATFISH (Clarias gariepinus) - Yeni Elisdiana; Dio Vinski Aquardo; Munti Sarida; Siti Hudaidah; Oktora Susanti; Maulid Wahid Yusup (University of Lampung, 2021)
One of the problems in North African Catfish (Clarias gariepinus) breeding is the inability to spawn spontaneously due to a specific spawning season. This happens due to reproductive dysfunction resulting in a slow development of gonads in catfish broodstock. This research aimed to study the effect of injection of pituitary gland extract from Striped Catfish head waste on the spawning performance of North Africans Catfish. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments were A (pituitary gland 0 mg/kg broodstock), B (pituitary gland 200 mg/kg broodstock), C (pituitary gland 300 mg/kg broodstock), and D (pituitary gland 400 mg/kg broodstock). The spawning process was performed with a ratio of 1:1 between male and female broodstock. The pituitary gland was injected into the head of female catfish at 07:30 pm and at 04:00 am. The research parameters observed were relative fecundity, fertilization rate (FR), hatching rate (HR), and survival rate (SR). The results showed that injection of the pituitary gland from Striped Catfish head waste could increase spawning performance with relative fecundity reaching of 31,357±12,265 eggs/ kg of female broodstock, FR 65±4%, HR 74±14%, and SR 81±10%. Therefore, hypophysation by utilizing Striped Catfish head waste is effectively increases the spawning performance of North African Catfish (Clarias gariepinus) seen from the high values of relative fecundity, FR, HR, and SR of larvae in treatment B (200 mg/kg broodstock).